2015
DOI: 10.1111/1756-185x.12645
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors in patients with connective tissue disease‐associated pulmonary hypertension diagnosed by echocardiography: results from a Korean nationwide registry

Abstract: In Korean patients with CTD-PH, the 3-year survival rate was 87%. Low diffusion capacity of carbon monoxide (DLCO), pleural effusion and diabetes mellitus were independent poor prognostic factors. Anti-UI-RNP antibody was protective. Prompt PAH-specific vasodilator therapy may improve the survival of patients with severe CTD-PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
4
27
1
Order By: Relevance
“…Our findings are in accordance with a cohort study in China which suggested that the most prevalent autoantibody was the anti‐U1RNP antibody in PAH associated with three major CTDs . The results from a Korean nationwide registry also revealed that anti‐RNP antibody was significantly associated with higher mortality …”
Section: Discussionsupporting
confidence: 91%
“…Our findings are in accordance with a cohort study in China which suggested that the most prevalent autoantibody was the anti‐U1RNP antibody in PAH associated with three major CTDs . The results from a Korean nationwide registry also revealed that anti‐RNP antibody was significantly associated with higher mortality …”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the presence of exercise induced pulmonary hypertension, assessed by exercise echocardiography, is independently associated with reduced survival in patients with valvular disease and could be useful to identify a high-risk subset of asymptomatic patients 35,36 . While RHC is the gold standard to assess pulmonary pressures and is required to confirm the diagnosis of PH, there is a need for safe and practical noninvasive clinical tests to screen at risk patients for PH.…”
Section: Discussionmentioning
confidence: 99%
“…Among the CTDs group, however, SLE patients had the best rates for 1-year survival (94% vs 82% for scleroderma and 88% for MCTD), although all patients had comparable hemodynamic characteristics at PAH diagnosis. Data from the Korean CTD-PAH registry, with 174 patients enroled, demonstrated that the 1- and 3-year survival were 90.7% and 87.3%, respectively 59. In that study, low D LCO , diabetes, and pleural effusion were poor prognostic factors, while anti-U1-RNP antibodies seemed to be protective.…”
Section: Prognosismentioning
confidence: 67%